Dynamics of social relations between Dayak Kenyah ethnic community in Rindang Benua Hamlet, Kaltim Prima Coal Ltd. and Balai Taman Nasional Kutai - Saputra, Raybie Ryan; Hermawati, Rina (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study examines the dynamics of social relations between the Dayak Kenyah ethnic community in Dusun Rindang Benua, the management of Kutai National Park (BTNK), and the CSR team of Kaltim Prima Coal within the conservation area of Kutai National Park. The researcher used an ethnographic method over 56 days, integrating an analytical framework that combines stages of social relations, patterns of social relations, and social capital to analyze the dynamics of the relations that emerge. Empirical evidence shows a distinction between trust and strategic compliance: community participation in conservation policies and CSR programs reflects both a willingness to cooperate and adaptive strategies within a context of power asymmetry. Social capital strengthens interactions between actors, yet it also reinforces existing hierarchies and encourages community dependency on the company. The CSR program contributes to social cohesion, but at the same time it generates community dependence on external assistance. The study concludes that the sustainability of social relations requires mechanisms that can amplify community voice in policy making and address structural dependency within asymmetric power relations between indigenous communities, state authorities, and corporations.   Penelitian ini mengkaji dinamika relasi sosial antara masyarakat etnis Dayak Kenyah di Dusun Rindang Benua, pengelola Taman Nasional Kutai (BTNK), dan tim CSR Kaltim Prima Coal Ltd. dalam kawasan konservasi Taman Nasional Kutai. Peneliti menggunakan metode etnografiselama 56 hari, penelitian mengintegrasikan kerangka analitis yang menggabungkan tahapan relasi sosial , pola relasi sosial, serta modal sosial untuk menganalisa dinamika relasi yang terjadi.Bukti empiris menunjukkan perbedaan antara trust dan upaya: partisipasi masyarakat dalam kebijakan konservasi dan program CSR menunjukkan niat kerja sama maupun strategi adaptif dalam konteks asimetri kekuasaan. Modal sosial memperkuat interaksi antar pihak, namun memperkuat hierarki yang sudah ada dan mendorong sifat ketergantungan masyarakat pada pihak perusahaan. Program CSR menunjukkan hasil pada kohesi sosial, namun program CSR juga menimbulkan ketergantungan masyarakat terhadap bantuan. Penelitian ini menyimpulkan bahwa keberlanjutan relasi sosial membutuhkan mekanisme yang dapat meningkatkan suara komunitas dalam perumusan kebijakan dan mengatasi ketergantungan struktural dalam relasi kuasa asimetri antara komunitas adat, otoritas negara dan korporat.